KERALASTIC: Biomechanical mapping of the human cornea for early detection and treatment monitoring of Keratoconus - (:unkn) unknown (My University, 2026)
Keratoconus is a degenerative disease that affects the human cornea and impairs the vision of populations at key ages for education and labor insertion. In Peru, incidence rates of Keratoconus are high (2 in 1000 individuals) compared to developed countri